Simultaneous Enhancement of the Activity and Durability of the Oxygen Reduction Reaction via Pd3Mo@Pt/C Catalysts - Yoo, Jaeyoung; Chan, Chen-Hui; Choi, Suyeon; Hong, Doosun; Paek, Sae Yane; Bang, Kihoon; Kim, Jong Min; Kim, Donghun; Han, Sang Soo; Lee, Hyuck Mo (American Chemical Society, 2025)
To overcome the limitations of conventional bimetallic catalysts in facilitating the oxygen reduction reaction (ORR), we employed density functional theory (DFT) screening to evaluate ternary Pd3X@Pt core@shell catalysts (X = transition metals), with the objective of increasing both the ORR activity and durability. Among the 25 candidates, Pd3Mo@Pt emerges as the most promising catalyst, showing a combination of a low limiting potential and a high dissolution potential. Experimental validation reveals that the carbon-supported Pd3Mo@Pt/C catalysts clearly exhibit exceptional mass activity (3.76 A mgPt -1) and specific activity (1.67 mA cm-2); these activities significantly surpass those of their Pt/C counterparts by factors of 10.2 and 3.18, respectively. Furthermore, these core@shell catalysts exhibit robust durability, while also exhibiting enhanced CO tolerance, as evidenced by CO stripping voltammetry. DFT calculations show that the superior activity and stability of Pd3Mo@Pt/C are attributed to the optimal modulation of the Pt surface electronic structures by the core elements, particularly Mo.